(untitled) (Fiep Bulletin - online, 2014)
Physical Education at School, because of the divergence among theoretical tendencies, methodological orientations and contents, comes across the objectives and appropriate contents to the student’s characteristics and needs, as programmatic orientations for the several educational levels. The references here presented, intend to subsidize Physical Education professionals of high school teaching in their curricular elaboration and to contribute with discussions and reflections on Physical Education didactic-pedagogic components, generating debate elements to the teaching-learning process. In the current Brazilian Education content, there are no doubts concerning the Physical Education importance in all different teaching levels. Facing those challenges it is necessary that Physical Education community defines capable objectives to legitimate the discipline in the high school context, in which the proposals, moreover assisting the students’ needs, should provide interesting situations and curiosities, producing a significant learning. To contribute in the formation of society process, we intend that the concepts, competences and abilities should be based in three thematic axes: language and corporal knowledge; corporal culture manifestations; and physical activity, health and life quality, which should constitute guiding topics to be worked in the discipline.